Integrasi Nilai-Nilai Al-Qur’an dalam Peningkatan Kreativitas dan Bahasa Anak Usia Dini melalui Media Plastisin dan Flashcard Digital - Alam Tarlam; Sukminah; Hernawati; Wina Astuty Evenia; Kokom Komariah (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the integration of Quranic values ​​in enhancing creativity and language skills in early childhood through the use of plasticine and digital flashcards at Al-Falah Kindergarten in West Pagaden District, Subang Regency. The background of this study is based on the importance of holistic stimulation of early childhood development in accordance with the principles of Quranic education, which emphasizes not only cognitive aspects but also creativity, language, and character development. This study used a qualitative descriptive method. The subjects consisted of 18 grade A children, consisting of 10 boys and 8 girls. Data collection techniques were conducted through observation, interviews with teachers, and documentation of children's work. The results showed that the use of plasticine can improve children's imagination, fine motor skills, and creativity. Meanwhile, Canva-based digital flashcards can improve children's receptive and expressive language skills through knowledge, pronunciation, and simple communication. The integration of Quranic verses, such as Surah Al-'Alaq verse 1 and Surah Al-'Alaq verse 2, is also supported by the use of digital flashcards. Verse 78 of An-Nahl, as a reinforcement of spiritual values, demonstrates the link between the creative learning process and the development of a child's religious character. Thus, creative media-based learning is relevant to Islamic educational principles and effective in developing a child's overall potential.